2019
DOI: 10.1038/s41598-019-55544-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of axial length and age on the visual outcome of patients with idiopathic epiretinal membrane after pars plana vitrectomy

Abstract: We evaluated predictive factors for visual outcomes in patients with idiopathic epiretinal membrane (iERM) after pars plana vitrectomy (PPV). Clinical records for 114 eyes (114 patients, mean age: 70.6 years) with iERM treated by PPV between March 2012 and March 2018 were retrospectively reviewed. Overall, the mean postoperative best-corrected visual acuity (BCVA) and central retinal thickness measured by optical coherence tomography improved as early as 1 month after surgery, and further improved until 3 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…We found that a shorter AL was a risk factor for PVR-C, irrespective of surgical invasion; PVR formation may progress easily in eyes with a shorter AL. The impact of a shorter AL on the vitreoretinal condition was discussed in our previous study; the visual outcome of iERM after pars plana vitrectomy was poor in eyes with a shorter AL, although the post-operative best-corrected visual acuity improved in comparison with the preoperative value [15]. We discussed that eyes with a shorter AL may have an undetached or incompletely detached posterior vitreous.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…We found that a shorter AL was a risk factor for PVR-C, irrespective of surgical invasion; PVR formation may progress easily in eyes with a shorter AL. The impact of a shorter AL on the vitreoretinal condition was discussed in our previous study; the visual outcome of iERM after pars plana vitrectomy was poor in eyes with a shorter AL, although the post-operative best-corrected visual acuity improved in comparison with the preoperative value [15]. We discussed that eyes with a shorter AL may have an undetached or incompletely detached posterior vitreous.…”
Section: Discussionmentioning
confidence: 67%
“…The J-RD Registry, which was established referring to previous population-based studies [14], collected data from 3446 participants with retinal detachment, who were registered at 26 qualified institutions. In this study, we analyzed the risk factors of patients who exhibited PVR at baseline, i.e., before surgery, and focused on the conditions of retinal detachment and native features of the eyes, i.e., axial length (AL), with the potential to affect the posterior vitreous condition, with respect to liquefaction and detachment [15]. We previously reported that a shorter AL was related to relatively poor postoperative visual outcomes in patients with an idiopathic epiretinal membrane (iERM).…”
Section: Introductionmentioning
confidence: 99%
“…None of these biomarkers can be tissue or disease specific, although their increased expression as well as just their presence can be of great diagnostic and prognostic value ( Strimbu and Tavel, 2010 ). Last, it is important to mention that some OCT parameters could be used to predict postoperative visual outcomes in patients with iERM treated with PPV ( Minami et al, 2019 ).…”
Section: Retinal Diseases: the Mechanisms Behind Clinical Manifestatimentioning
confidence: 99%
“…Several studies have demonstrated a remarkable improvement in vision and life quality after ERM surgeries. [7][8][9][10] Therefore, ERM surgeries are essential for elderly patients. However, for some elders, advanced age remains a barrier to undergo ERM surgery.…”
Section: Introductionmentioning
confidence: 99%